Risco ocupacional relacionado ao conforto ambiental em UTIs - Vieira, Elamara Marama de Araujo (2016)
Insalubrious buildings concerning the environmental aspect may cause a range of diseases for the occupants, which may affect the physical and/or mental health. In the Intensive Care Unit (ICU), attention. agility, and concentration required for task execution become an aggravating factor and, jointly with adverse environment conditions, may harm the health and well-being of the professionals, which can start multiple symptoms. Thus, physical environment where the professional is inserted becomes an important quantitative indicator of risk exposure in order to assess how the professional is being affected by environmental comfort requirements. It aims to assess if the environmental variables offer risk to health and well-being of the professionals at Intensive Care Units. Nine ICUs were selected in the city of João Pesssoa, where data were collected in three consecutive days regarding the thermal, acoustics, lighting, and air quality variables. Simultaneously, 128 professionals were interviewed, among physicians, nurses, physiotherapists, and nurse technicians, addressing issues related to perception. satisfaction. and health conditions related to the environment. Data descriptive analysis relating to environmental variables collected in each ICU was done through Bayesian networks and it was analyzed their influence on health and well-being of the professionals. Five Bayesian networks were built: one in global nature that approaches the experimental variables: temperature, noise, lighting, and air quality, the relative perception for each variable, beyond signs and symptoms of the professionals raised through the questionnaires; the other four focused each variable of approached environmental comfort. Each network was validated according to ROC (Receiver Operating Characteristic) curve, considering the value under the curve ≥ 0,7 as satisfactory. The variables that presented greater impacts on professionals’ health were the thermal variables, be they experimental or perceptual. Global Bayesian Network (GBN) enabled to verify that to go from a comfort to a discomfort thermal status, according to ISO PMV (Predicted Mean Vote) 7730/2005, might increase in +8% the risk for emergence of symptoms. According to GBN. a professional may leave from a thermal comfort status, according to professionals’ perception. it might increase in +11.4% the risk for appearance of physical symptoms, and in +7.6% the appearance of psychological symptoms. In the specific Bayesian network of thermal variables, the inclusion of nodes related to the wish and thermal feeling could consolidate the idea that neutrality and acceptance of thermal environment are essential qualities to minimize 7 symptomatological complaints, which can increase in up +27% the probability of symptoms occurrence. It was determined that environmental variables have impact on health and well-being of the intensivists professionals, which may favour or inhibit the occurrence of symptomatological complaints. Perception is positioned between man and environment, or still as the own predictive in cases where even great status the negative perception may result in symptoms. It is admissible that the matter in question involves a superior complexity to the approached demand in the moment. The occurrence of occupational symptomatological complaints related to the environment, be they physical or psychological, involves a greater diversity of the approached variables in this research, including personal, cognitive, and organizational variables, which may be addressed in future investigations.